Difference between revisions of "1984 USAMO Problems/Problem 1"
(→Solution) |
(→Solution) |
||
Line 9: | Line 9: | ||
Solution #1 | Solution #1 | ||
− | Using Vieta's formulas, we have: | + | Using Vieta's formulas, we have: |
− | + | <math>\begin{align*}a+b+c+d &= 18,\\ ab+ac+ad+bc+bd+cd &= k,\\ abc+abd+acd+bcd &=-200,\\ abcd &=-1984.\\ \end{align*}</math> | |
− | + | ||
+ | From the last of these equations, we see that <math>cd = \frac{abcd}{ab} = \frac{-1984}{-32} = 62</math>. Thus, the second equation becomes <math>-32+ac+ad+bc+bd+62=k</math>, and so <math>ac+ad+bc+bd=k-30</math>. The key insight is now to factor the left-hand side as a product of two binomials: <math>(a+b)(c+d)=k-30</math>, so that we now only need to determine <math>a+b</math> and <math>c+d</math> rather than all four of <math>a,b,c,d</math>. | ||
− | Therefore, we have (\underbrace{a+b}_4)(\underbrace{c+d}_{14}) = k-30, yielding k=4\cdot 14+30 = \boxed{86}. | + | Let <math>p=a+b</math> and <math>q=c+d</math>. Plugging our known values for <math>ab</math> and <math>cd</math> into the third Vieta equation, <math>-200 = abc+abd + acd + bcd = ab(c+d) + cd(a+b)</math>, we have <math>-200 = -32(c+d) + 62(a+b) = 62p-32q</math>. Moreover, the first Vieta equation, <math>a+b+c+d=18</math>, gives <math>p+q=18</math>. Thus we have two linear equations in <math>p</math> and <math>q</math>, which we solve to obtain <math>p=4</math> and <math>q=14</math>. |
+ | |||
+ | Therefore, we have <math>(\underbrace{a+b}_4)(\underbrace{c+d}_{14}) = k-30, yielding k=4\cdot 14+30 = \boxed{86}</math>. | ||
Solution #2 (sketch) | Solution #2 (sketch) | ||
− | We start as before: ab=-32 and cd=62. We now observe that a and b must be the roots of a quadratic, x^2+rx-32, where r is a constant (secretly, r is just -(a+b)=-p from Solution #1). Similarly, c and d must be the roots of a quadratic x^2+sx+62. | + | We start as before: <math>ab=-32</math> and <math>cd=62</math>. We now observe that a and b must be the roots of a quadratic, <math>x^2+rx-32</math>, where r is a constant (secretly, r is just -(a+b)=-p from Solution #1). Similarly, c and d must be the roots of a quadratic <math>x^2+sx+62</math>. |
+ | |||
+ | Now | ||
+ | |||
+ | <math><cmath> \begin{align*}x^4-18x^3+kx^2+200x-1984 &= (x^2+rx-32)(x^2+sx+62)\\ & = x^4+(r+s)x^3+(62-32+rs)x^2+(62s-32r)x-1984.\end{align*} </cmath></math> | ||
− | + | Equating the coefficients of <math>x^3</math> and <math>x</math> with their known values, we are left with essentially the same linear equations as in Solution #1, which we solve in the same way. Then we compute the coefficient of <math>x^2</math> and get <math>k=\boxed{86}.</math> | |
==See Also== | ==See Also== |
Revision as of 21:28, 27 April 2014
Problem
In the polynomial , the product of of its roots is . Find .
Solution
Let the four roots be , so that . From here we show two methods; the second is more slick, but harder to see.
Solution #1
Using Vieta's formulas, we have:
$\begin{align*}a+b+c+d &= 18,\\ ab+ac+ad+bc+bd+cd &= k,\\ abc+abd+acd+bcd &=-200,\\ abcd &=-1984.\\ \end{align*}$ (Error compiling LaTeX. ! Package amsmath Error: \begin{align*} allowed only in paragraph mode.)
From the last of these equations, we see that . Thus, the second equation becomes , and so . The key insight is now to factor the left-hand side as a product of two binomials: , so that we now only need to determine and rather than all four of .
Let and . Plugging our known values for and into the third Vieta equation, , we have . Moreover, the first Vieta equation, , gives . Thus we have two linear equations in and , which we solve to obtain and .
Therefore, we have .
Solution #2 (sketch)
We start as before: and . We now observe that a and b must be the roots of a quadratic, , where r is a constant (secretly, r is just -(a+b)=-p from Solution #1). Similarly, c and d must be the roots of a quadratic .
Now
$<cmath> \begin{align*}x^4-18x^3+kx^2+200x-1984 &= (x^2+rx-32)(x^2+sx+62)\\ & = x^4+(r+s)x^3+(62-32+rs)x^2+(62s-32r)x-1984.\end{align*} </cmath>$ (Error compiling LaTeX. ! Package amsmath Error: \begin{align*} allowed only in paragraph mode.)
Equating the coefficients of and with their known values, we are left with essentially the same linear equations as in Solution #1, which we solve in the same way. Then we compute the coefficient of and get
See Also
1984 USAMO (Problems • Resources) | ||
Preceded by First Problem |
Followed by Problem 2 | |
1 • 2 • 3 • 4 • 5 | ||
All USAMO Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.